The Salience of Vomiting in Teenagers Binge Drinking Intentions - Pettigrew, Simone; Pescud, M.; Jarvis, W.; Webb, D. (Australian & New Zealand Marketing Academy, 2009)
Binge drinking among Australian teenagers has been identified as a serious health issue. Unfortunately, efforts to date to address this problem have been largely ineffective. It has been suggested that using images of teenagers vomiting in social marketing campaigns isn’t effective because vomiting is viewed as a positive outcome due its ability to signify a ‘big night’. The present study accessed online information posted by Australian teenagers to explore alcohol-related beliefs and behaviours that are reported online. A thematic analysis of the blogs suggests that for many Australian teenagers vomiting is still a deterrent to heavy drinking, and that they may be turning to illicit drugs to achieve an altered mental state with a lower risk of vomiting.